2022
DOI: 10.3390/agriculture12101724
|View full text |Cite
|
Sign up to set email alerts
|

Scenarios for Sustainable Farming Systems for Macadamia Nuts and Mangos Using a Systems Dynamics Lens in the Vhembe District, Limpopo South Africa

Abstract: Agriculture is arguably one of the most important economic sectors for South Africa’s development as it is directly linked to food security. Farming systems in South Africa have been characterized by a duality where large-scale commercial farmers and small-scale farmers co-exist. The conventional approach to understanding agricultural production in the country has always viewed the two farming systems as mutually exclusive. The study argues that there are various points of interaction between the two kinds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The authors proposed that small-scale rice farmers are the main body of agricultural production and yet lack modern agricultural technology and knowledge; therefore, the government should pay more attention to and train small-scale farmers to ensure national food security and promote agricultural sustainability. From the perspective of system dynamics, Mary Scholes et al [15] analyzed and evaluated the small-scale and large-scale farming systems of mangoes and nuts in the Vhembe district of Limpopo South Africa, and found that small-scale and large-scale farming systems can work together to achieve food security at all levels. They also proposed that large-scale and small-scale farming systems work collaboratively rather than independently.…”
Section: Practical Experience Of Agricultural Sustainable Developmentmentioning
confidence: 99%
“…The authors proposed that small-scale rice farmers are the main body of agricultural production and yet lack modern agricultural technology and knowledge; therefore, the government should pay more attention to and train small-scale farmers to ensure national food security and promote agricultural sustainability. From the perspective of system dynamics, Mary Scholes et al [15] analyzed and evaluated the small-scale and large-scale farming systems of mangoes and nuts in the Vhembe district of Limpopo South Africa, and found that small-scale and large-scale farming systems can work together to achieve food security at all levels. They also proposed that large-scale and small-scale farming systems work collaboratively rather than independently.…”
Section: Practical Experience Of Agricultural Sustainable Developmentmentioning
confidence: 99%
“…In both regions, households farmed on communal land and none of them owned the land, which is common in other South African homelands as well (Kepe and Tessaro, 2014). Farming in the communities was primarily pursued by older women, as is generally the case in small-scale farming across the country (Mkuhlani et al, 2019;Materechera and Scholes, 2022). However, the farming systems in the two regions differed, particularly in the dependency of households on farming for food provisioning.…”
Section: Diversity Of Small-scale Farming Systemsmentioning
confidence: 99%
“…The differences between these regions demonstrate the important knowledge gap regarding-how, under what context, and which forms of agricultural interventions-may complement rural development efforts and contribute to the rural economy. This is of great consequence, especially to the country's ongoing land reform debates (Materechera and Scholes, 2022).…”
Section: Diversity Of Small-scale Farming Systemsmentioning
confidence: 99%